Targeting the Roots of Psychosis: The Role of Aberrant Salience - Giuseppe Marano; Francesco Maria Lisci; Greta Sfratta; Ester Maria Marzo; Francesca Abate; Gianluca Boggio; Gianandrea Traversi; Osvaldo Mazza; Roberto Pola; Eleonora Gaetani; Marianna Mazza (Pediatric Reports)
Aberrant salience, defined as the inappropriate attribution of significance to neutral stimuli, is increasingly recognized as a critical mechanism in the onset of psychotic disorders. In young individuals at ultra-high risk (UHR) for psychosis, abnormal salience processing may serve as a precursor to full-blown psychotic symptoms, contributing to distorted perceptions and the onset of psychotic ideation. This review examines current literature on aberrant salience among UHR youth, exploring its neurobiological, psychological, and behavioral dimensions. Through a comprehensive analysis of studies involving neuroimaging, cognitive assessments, and symptomatology, we assess the consistency of findings across diverse methodologies. Additionally, we evaluate factors contributing to aberrant salience, including neurochemical imbalances, dysregulation in dopamine pathways, and environmental stressors, which may jointly increase psychosis vulnerability. Identifying aberrant salience as a measurable trait in UHR populations could facilitate earlier identification and targeted interventions. Implications for clinical practice are discussed, highlighting the need for specialized therapeutic approaches that address cognitive and emotional dysregulation in salience attribution. Recent research underscores the importance of aberrant salience in early psychosis research and advocates for further studies on intervention strategies to mitigate progression to psychosis among UHR individuals.